Quality improvement of screen-printed Al emitter by using SiO2 interfacial layer for industrial n-type silicon solar cells. (August 2015) - Wei, Yi; Li, Ping; Wang, Yuxuan; Tan, Xin; Song, Chengyuan; Lu, Chunxi; Zhao, Zengchao; Liu, Aimin
Highlights: An interfacial thin SiO2 layer is formed between Si and Al. The SiO2 layer mitigates the inhomogeneous Al diffusion during alloying process. The thin SiO2 layer improves the pn junction quality and transport properties. An 18.8% efficient solar cell with improved photovoltaic performances is achieved. Abstract: This paper reports on an industrially applicable approach to create efficient Al-doped p + regions alloyed from screen-printed pastes for the application as rear emitters in n -type silicon solar cells. The influences of polished and pyramidal rear surfaces on the formation of Si–Al alloy and saturation current are discussed. We demonstrate that a thin SiO2 layer on Si–Al interface can mitigate the inhomogeneous Al diffusion during alloying process and develop the transport properties. Furthermore, we apply this SiO2 layer in our n + np + solar cells, which exhibit lower series resistance and fine IQE response as a result of the improved Al emitter quality. For large-area n -type silicon solar cells (239 cm 2 ) with a full-area Al- p + rear emitter, we achieved an 18.8% efficient cell with an open-circuit voltage of 637.4 mV. Remarkable gains of 1.6% on average efficiency, 0.8 mA/cm 2 on J sc, 8.6 mV on open-circuit voltage and 4.1% on FF are obtained, comparing with the solar cells fabricated by standard industrial process.